TINDAK PIDANA PEMALSUAN SERTIFIKASI PRODUK DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN (Studi Kasus di Pengadilan Negeri Medan) - Trisna, Wessy; Syahputra, M.Yusrizal Adi; Tampubolon, Otto Paiantua (Universitas Medan Area, 2014)
Law enforcement against businesses that fabricate products in terms oflaw No. 8 of 1999 about consumer protection, then against the perpetrators ofemployers who perform these action can requested compensation by consumersbecause such actions are contrary to the provisions of law protection consumer.The compensation must be reported solely by consumers to relevant authoritiesis Consumer Dispute Resolution in the jurisdiction in which product is feared tobe sertificate.